2020
DOI: 10.1371/journal.pone.0237740
|View full text |Cite
|
Sign up to set email alerts
|

The impact of properly diagnosed sarcopenia on postoperative outcomes after gastrointestinal surgery: A systematic review and meta-analysis

Abstract: Background Sarcopenia is defined as the loss of muscle mass combined with loss of muscle strength, with or without loss of muscle performance. The use of this parameter as a risk factor for complications after surgery is not currently used. This meta-analysis aims to assess the impact of sarcopenia defined by radiologically and clinically criteria and its relationship with complications after gastrointestinal surgeries. Materials and methods A review of the literature was conducted in accordance with the Prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 57 publications
1
33
2
Order By: Relevance
“…A significantly higher risk for postoperative complications was found in emergency surgery (RR = 2.07, 4 studies, 734 patients [ 29 ]) and in surgery for inflammatory bowel disease (OR = 6.097, 10 studies, 885 patients [ 30 ]). The morbidity was also increased after gastrectomy (OR 3.09, 8 studies, 2649 patients [ 31 ]) and after colorectal resections (OR 2.71, 2 studies, 518 patients [ 31 ] but a higher risk of postoperative complications has not been identified after esophageal (OR 0.81, 8 studies, 1488 patients [ 32 ]) and pancreatic resections (13 studies, 3608 patients [ 33 ]). All commonly used CT-assessed sarcopenia indexes, such as the skeletal muscle index (SMI), predict the risk of major postoperative complications (RR 1.36, 22 studies, 6656 patients [ 34 ]).…”
Section: Discussionmentioning
confidence: 99%
“…A significantly higher risk for postoperative complications was found in emergency surgery (RR = 2.07, 4 studies, 734 patients [ 29 ]) and in surgery for inflammatory bowel disease (OR = 6.097, 10 studies, 885 patients [ 30 ]). The morbidity was also increased after gastrectomy (OR 3.09, 8 studies, 2649 patients [ 31 ]) and after colorectal resections (OR 2.71, 2 studies, 518 patients [ 31 ] but a higher risk of postoperative complications has not been identified after esophageal (OR 0.81, 8 studies, 1488 patients [ 32 ]) and pancreatic resections (13 studies, 3608 patients [ 33 ]). All commonly used CT-assessed sarcopenia indexes, such as the skeletal muscle index (SMI), predict the risk of major postoperative complications (RR 1.36, 22 studies, 6656 patients [ 34 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia has been reported to be associated with adverse post-surgical outcomes in many medication conditions. In 2020, a meta-analysis reported an elevated risk of complications and readmissions in patients with sarcopenia after any type of gastrointestinal surgery [ 39 ]. Similarly, another meta-analysis pointed out that sarcopenia independently predicted shorter survival and increased mortality among patients undergoing urologic oncology surgeries [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mitura et al 26 observed that the occurrence and intensity of pain was significantly higher in younger patients. Other characteristics may play a role, not only in pain, but also morbidity and mortality, this include smoking 27 , previous intestinal resection 28 and concomitant diseases 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%